Infectious Diseases of Poverty, the first five years - Wei Wang; Jin Chen; Hui-Feng Sheng; Na-Na Wang; Pin Yang; Xiao-Nong Zhou; Robert Bergquist (BMC, 2017)
Abstract Although the focus in the area of health research may be shifting from infectious to non-communicable diseases, the infectious diseases of poverty remain a major burden of disease of global health concern. A global platform to communicate and share the research on these diseases is needed to facilitate the translation of knowledge into effective approaches and tools for their elimination. Based on the "One health, One world" mission, a new, open-access journal, Infectious Diseases of Poverty (IDP), was launched by BioMed Central in partnership with the National Institute of Parasitic Diseases (NIPD), Chinese Center for Disease Control and Prevention (China CDC) on October 25, 2012. Its aim is to identify and assess research and information gaps that hinder progress towards new interventions for a particular public health problem in the developing world. From the inaugural IDP issue of October 25, 2012, a total of 256 manuscripts have been published over the following five years. Apart from a small number of editorials, opinions, commentaries and letters to the editor, the predominant types of publications are research articles (69.5%) and scoping reviews (21.5%). A total of 1 081 contributing authors divided between 323 affiliations across 68 countries, territories and regions produced these 256 publications. The journal is indexed in major international biomedical databases, including Web of Science, PubMed, Scopus and Embase. In 2015, it was assigned its first impact factor (4.11), which is now 2.13. During the past five years, IDP has received manuscripts from 90 countries, territories and regions across six continents with an annual acceptance rate of all contributions maintained at less than 40%. Content analysis shows that neglected tropical diseases (NTDs), followed by the "Big Three" (HIV/AIDS, malaria and tuberculosis) and infectious diseases in general comprise 88% of all publications. In addition, a series of 10 thematic issues, covering 118 publications in all, was published as separate parts of the first five volumes. These publications were cited 975 times, which equals an average of 8.3 times per publication. The current challenge is to identify cutting-edge research topics and attract and to publish first-rate publications leading to increasing importance and impact of the journal in its field.